Antibiotics Used for Upper Respiratory Tract Infection: a Case Study at a Primary Health Center Bogor Indonesia - Wiwi Ambarwati; Vivi Setiawaty; Adik Wibowo (Universitas Islam Bandung, 2018)
Acute upper respiratory tract infection (URTI) is one of the health problem in a community with high prevalence and healthcare cost. At the primary health center (PHC), URTI is one of the most common diseases with a prevalence 45.64% in Bogor city on 2015, while Basic Health Research 2013 data showed the prevalence of URTI in Indonesia by 25%. This study analyzes the antibiotic prescription for URTI patients, factors influencing the rationale of antibiotic prescriptions, and the rational use of medicine (RUM) program management at Primary Health Centers at Bogor city. The research was analytic descriptive cross-sectional study by collecting data from medical records of patients diagnosed with non-pneumonia URTI, observation for outpatient health care, and interview with all responsible persons. The data were collected on 16 April–20 May 2018 from primary health centers at Bogor city. The samples were 359 oral antibiotic prescriptions of three physicians and antibiotics were prescribed for 122 (34%) cases from 359 cases of which 102 were evaluated for rationality according to local guidelines issued by the Ministry of Health Republic of Indonesia. The URTI diagnosis is classified into few categories with the prevalence of nasopharyngitis (62.9%), pharyngitis (30.6%), tonsillitis (5.3%), and sinusitis and acute otitis media (0.6%). Most antibiotics used were amoxicillin and cefadroxil. This study revealed that antibiotics prescribed 88% inaccuracy of antibiotics duration, 12% incompatibility with the guidance of antibiotic, 3% incompatibility with guidance and imprecise duration, and 1% inaccuracy of dose. Some factors that influencing rationality of antibiotics prescription was lack of physician's adherence to the clinical guideline, pharmacist role was not optimal, and lack of monitoring evaluating. PENGGUNAAN ANTIBIOTIK UNTUK INFEKSI SALURAN PERNAPASAN ATAS: STUDI KASUS DI PUSAT KESEHATAN PRIMER BOGOR INDONESIAInfeksi saluran pernapasan atas (ISPA) akut adalah salah satu masalah kesehatan dengan prevalensi dan biaya perawatan kesehatan yang tinggi. Di pusat kesehatan masyarakat (puskesmas), ISPA adalah salah satu penyakit yang paling umum dengan prevalensi 45,64% di Kota Bogor pada tahun 2015, sementara data Riset Kesehatan Dasar 2013 menunjukkan prevalensi ISPA di Indonesia sebesar 25%. Penelitian ini menganalisis resep antibiotik untuk pasien ISPA, faktor yang memengaruhi dasar pemberian antibiotik, dan penggunaan manajemen program pengobatan rasional di puskesmas di Kota Bogor. Penelitian ini adalah penelitian deskriptif analitik cross-sectional dengan mengumpulkan data rekam medis pasien yang didiagnosis nonpneumonia ISPA, observasi perawatan kesehatan rawat jalan, dan wawancara. Data dikumpulkan pada 16 April–20 May 2018 dari puskesmas di Kota Bogor. Sampel adalah 359 resep antibiotik oral dari tiga dokter dan antibiotik diresepkan untuk 122 (34%) kasus dari 359 kasus yang 102 di antaranya dievaluasi untuk rasionalitas sesuai dengan pedoman yang dikeluarkan oleh Kementerian Kesehatan Republik Indonesia. Beberapa penyakit yang termasuk ISPA menunjukkan prevalensi nasofaringitis (62,9%), faringitis (30,6%), tonsilitis (5,3%), serta sinusitis dan otitis media akut (0,6%). Mayoritas antibiotik yang digunakan adalah amoksisilin dan sefadroksil. Penelitian ini mengungkapkan bahwa antibiotik yang diresepkan 88% tidak tepat durasi, 12% tidak cocok dengan panduan, 3% tidak cocok dengan panduan dan tidak tepat durasi, serta 1% tidak tepat dosis. Simpulan, faktor yang memengaruhi rasionalitas resep antibiotik adalah kurangnya kepatuhan dokter terhadap pedoman klinis, peran apoteker tidak optimal, dan pemantauan evaluasi yang kurang.